2019
DOI: 10.1097/01.asw.0000604176.47082.60
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Chronic Lower Extremity Ulcers with Allogeneic Platelet-Rich Plasma and Artificial Dermis: A Case Report

Abstract: Hydroxyurea is an oral medication associated with painful, nonhealing ulcers, for which there is no effective treatment but permanent discontinuation of hydroxyurea. The authors present a case of leg ulcers that likely occurred as a result of hydroxyurea use in a patient with essential thrombocythemia. Topical treatment with allogeneic platelet-rich plasma and artificial dermis completely healed the leg ulcers without hydroxyurea cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…However, in patients treated with hydrogel, a significant change was noted only at six weeks, indicating better granulation tissue formation with PRP. Clinically appreciable granulation tissue formation following treatment with PRP has been reported by various researchers [15,[22][23][24][25]. Back in 1986, Knighton et al demonstrated accelerated growth of granulation tissue and epithelization in chronic non-healing wounds following topical application of autologous platelet-derived wound healing factors [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, in patients treated with hydrogel, a significant change was noted only at six weeks, indicating better granulation tissue formation with PRP. Clinically appreciable granulation tissue formation following treatment with PRP has been reported by various researchers [15,[22][23][24][25]. Back in 1986, Knighton et al demonstrated accelerated growth of granulation tissue and epithelization in chronic non-healing wounds following topical application of autologous platelet-derived wound healing factors [26].…”
Section: Discussionmentioning
confidence: 99%
“…Among the other wounds treated (n = 10, 43.6%), infections developed a third of cases (n = 8, 34.8%) and the treatment was discontinued in two (8.7%). While our group has gained experience in the management of PRP obtained from donors since January 2012 [36], and in particular has used ABO-identical platelets from single healthy donors with promising results [31], we have only reported our work regarding their use for skin ulcers and secondary mandibular osteonecrosis at scientific meetings [36]. We emphasize that this current work with new recruited patients continues our previous studies and also the results are now consistent and support the previous results obtained.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, Zhao et al [31] were the first to report successful treatment of hydroxyurea-related chronic lower extremity ulcers with single-donor al-PRP, in their case, using a donor with lineal consanguinity. They described a patient with ET treated with hydroxyurea whose clinical diagnosis was perplexing [31].…”
Section: Use Of Al-prp Vs Au-prp In the Treatment Of Chronic Woundsmentioning
confidence: 99%
See 2 more Smart Citations